CIVIL RESPONSIBILITY OF ELECTRONIC DOCUMENTATION BODIES (A COMPARATIVE STUDY) - Assist. Legal Consultant Ali Hassan Alwan (Scholar Express Journals, 2023)
The emergence of electronic communication as a new tool for the conclusion of legal acts and the completion of commercial transactions is one of the most important manifestations of the scientific and technological development or the so-called information revolution. However, this development in the conclusion of legal actions was matched by the evolution of the penetration of this behavior which is made through these means and make them vulnerable for the change and forgery, which generated the feeling of dealers lack of seriousness and lack of elements of safety and confidentiality, so has developed electronic authentication system, which is the cornerstone in this place, which is committed to document the authenticity of the conduct issued by the person via electronic means And intention and to ensure that it is not possible to tamper with the information subject matter of conduct and issuing an electronic document attesting to this, all through competent authorities of duty not to favor one of the dealers at the expense of the other named electronic authentication. However, the electronic authentication authorities may interfere in their investigation of the health and safety of the actions carried out by these means and issue a certificate of authentication that is not in accordance with reality, and then the issue of the obligation that these parties will bear and the extent of their responsibility towards the affected customers. Through its definition and the definition of its conditions and the parties and the services provided by these entities, and we will also review the nature of the responsibility of these entities if it was a contractual or liability
Keywords: electronic authentication; contractual liability; tort liability